Cultural heritage in social media : Museum of Photography - Rinne, Silvia (2012)
The research Cultural Heritage in Social Media: Museum of Photography deals with a new form of displaying and preserving cultural heritage in the 21st century by using social media tools. This paper is an analysis of a Romanian cultural heritage blog, Museum of Photography, which contains documentary photography from the end of the 19th century until 1990’s as well as other types of photographs related to the interests’ of Alex Galmeanu – the owner of Museum of Photography. The aim of this research is to demonstrate that cultural heritage exists outside the boundaries of formal institutions, namely museums, thus showing that the meaning of the word “museum” is expanding and that the public can be successfully involved in online heritage projects. Furthermore it offers a new insight on the environment where cultural heritage is encountered, how cultural heritage infiltrated in social media, how people respond to this phenomenon and what possible future outcomes this might have. The main research question is: how is cultural heritage represented in social media and what implications does this representation have on community and heritage itself? The research method is qualitative-ethnographic which enables the researcher to offer a general understanding of the way in which cultural heritage is represented in social media through blogging. In addition, the research uses a case study for a closer analysis of this new phenomenon, offering as examples for analysis blog posts and comments. All the text quotes from the blog are translated from Romanian to English with further explanations regarding the cultural context. Moreover, a questionnaire is also sent to readers of Museum of Photography asking for their opinions on the blog and its content and offering additional information about its public. Museum of Photography was proven to be a successful way of preserving and displaying cultural heritage outside formal institutions and a proof that cultural heritage can also be displayed online due to people’s interest and enthusiasm for their own past. This blog sustains the idea that cultural heritage can be presented under a popular, unrestricted, free form and proves that a “museum” is not only a physical institution but a concept that is further developed with great results. The problems encountered with this research were the negative aspects of displaying cultural heritage online, namely data inaccuracy due to the fact that Museum of Photography is an amateur project, disrespectful remarks encountered in the blog comments as well as issues of long-term preservation.